Spatial Interaction in an Urban-rural Setting: A Case Study of Agbor and its Rural Environs - Ikpo, Eugene Dike (Obafemi Awolowo University, 2014)
This dissertation examined the validity of the hypothesis that the conditions of complementarities, absence of intervening opportunity and transferability, must be satisfied before interaction occurs between spatial units. The research setting was the region comprising Agbor and four rural settlements -Umunede, Owa-Alero, Uteokpu and Abavo. Observational and questionnaire surveys were conducted. Spatial and socio-economic variables from the questionnaire survey were used in the subsequent description and analyses of interaction networks and facilities in the study area through potential and Gravity model applications and correlation analysis.